Effect of a Ketogenic Diet on Some Biochemical Parameters in Obese People - Al-Fayyadh, Mohanad S. (Iraqi Journal of Science, 2023)
This study examined the effects of a few biochemical variables on obese Iraqi males and females with a 30.5 body mass index (BMI) when they were fed a ketogenic diet. The present study demonstrates how an individual who follows a ketogenic diet has an increase in low-density lipoprotein (LDL-cholesterol). This research’s objective was to assess the levels of some biochemical variables in obese people who were eating a ketogenic diet. Following 35 days on a ketogenic diet, the results show a significantly higher P ≤ 0.05 level of low-density lipoprotein (LDL) and total cholesterol (TC). Additionally, insulin, fasting blood sugar (FBS), cortisol, HOMA-IR, urea, BMI, and creatinine all show a considerable reduction, P ≤ 0.05.